THE USE OF CORRECTIVE FEDDBACK TO TEACH STUDENTS’ WRITING ABILITY - Rita Marlina (Journal of English Education, Literature and Linguistics, 2018)
The objective of this research is to find out the influence of corrective feedback toward students’ writing ability. This research is true experimental research. The sampling technique used simple random sampling. In collecting the data, researcher used writing test to know the students’ ability in writing. The data were analyzed by using SPSS 19. Based on the result of data analysis, there is an influence to teach students’ writing ability using corrective feedback at tenth grade students’ of SMAN 1 Air Naningan in the academic year 2017/2018. It can be proved by the result of t-test formula. It is showed that the significant level of 5% (0,05) gets 8.08838 > 1.99656. Based on the result above, the use of corrective feedback to teach students’ writing ability had significant influence.